Rehabilitation Retrospect - Ministry of Rehabilitation Government of India (Ministry of Rehabilitation Government of India, 1957)
Among the many great and significant, events which have marked the growth of our country, few can compare in importance and significance with the Partition of India into the Dominions of India and Pakistan which took place on August 15, 1947. On the long road receding into the past, which is the history of our country, this date is a milestone which marks not merely a stage in our progress as a nation, but a critical cross-road.
Ministry of Rehabilitation Government of India
Ministry of Rehabilitation Government of India